2001
DOI: 10.3408/jasti.5.85
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Sheet glass samples were collected from diŠerent sources of 3 domestic manufacturers in Japan. Refractive index (RI) was measured for the evaluation of source discrimination capability of them. Variation of RI value within a sheet glass, which was calculated from RI measurement for the fragments taken from 5 diŠerent position in each of 4 sheet glass samples, was 1.9×10 by standard deviation at maximum. A pair of sheet glass samples was considered to be distinguishable when they oŠered diŠerence in RI value mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…It is reported that the variation of RI within a sheet glass across different sampling positions is smaller than 0.0002, which was calculated as the maximum range of the mean ± 2SD. 9,14 Compared with the inner-sample variation, RI for the 11 sheet glasses occurred over a wide range from 1.5186 to 1.5204. Discrimination of these glasses was performed as follows.…”
Section: Results Of Ri Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that the variation of RI within a sheet glass across different sampling positions is smaller than 0.0002, which was calculated as the maximum range of the mean ± 2SD. 9,14 Compared with the inner-sample variation, RI for the 11 sheet glasses occurred over a wide range from 1.5186 to 1.5204. Discrimination of these glasses was performed as follows.…”
Section: Results Of Ri Measurementsmentioning
confidence: 99%
“…[1][2][3] The forensic discrimination of glass fragments has been carried out by comparing the color and thickness, 4 observing the original surface under an interference microscope, 5 and measuring the refractive index (RI) and density. [6][7][8][9][10] However, a comparison of the optical and morphological characteristics can be applied only to sufficiently large fragments, which are rarely found in actual cases. Improvements in quality control during the manufacturing of glass have made the variation for RI of glass smaller, resulting in a reduced discrimination capability by the comparison of RI.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of RI was repeated 5 times for each sample using different fragments. 10 Analysis of trace elements by ICP-MS. Each piece of a glass sample was washed with ethanol and water before use. After being dried in an oven, this piece was crushed into smaller fragments of appropriate size (approximately 2 mg or smaller) with an agate mortar.…”
Section: Methodsmentioning
confidence: 99%
“…It is reported that variation of RI within a pane of sheet glass is less than 0.0002. 8,10 Two pieces of glass fragments are considered to originate from different sources when they provide a larger difference in RI than this decision range of identity. The difference in RI between the heated and non-heated glasses obtained by this experiment is approximately from 6 to 7 times larger than the decision range of identity.…”
Section: Effect Of Heating On Ri Of Glassmentioning
confidence: 99%
See 1 more Smart Citation